Survey of Intravitreal Injection Practice Patterns Among Retina Specialists. (July 2020) - Sassalos, Thérèse M.; Patel, Nish; Andrews, Chris; Smith, Stephen J.; Musch, David C.; Besirli, Cagri G.
Purpose: Intravitreal injection therapy (IVT) is the most performed procedure in ophthalmology. This study was conducted to determine current trends in IVT delivery. Methods: An online, 31-question, multiple-choice survey was sent to 1677 retina specialists. The survey consisted of 3 sections: general questions, procedure technique, and postprocedure technique. Results: A total of 264 (16%) retina specialists completed the survey. The use of povidone-iodine (100%) and small-gauge needles (97%) was common, whereas ocular anesthesia was split among lidocaine gel (31%), lidocaine drops (25%), subconjunctival lidocaine (28%), and lidocaine-soaked pledgets (15%). More than 85% indicated povidone-iodine contributes to post-IVT corneal toxicity, and 12% reported that a needlestick injury to physician or staff occurred during IVT. Conclusions: Key areas for IVT improvement include optimized ocular anesthesia, development of a guarded needle for ocular drug delivery, and formulation of a less toxic ocular antiseptic.